2002
DOI: 10.1016/s0840-4704(10)60177-9
|View full text |Cite
|
Sign up to set email alerts
|

Long Stay Patients in Winnipeg Acute Care Hospitals

Abstract: Risk factors for long-stays (more than 30 days) in Winnipeg hospitals were identified, including sociodemographic, illness, and system characteristics. The largest determinant of length of stay was discharge destination; discharge to a nursing home increased length of stay by 173% and 89% for medical and surgical patients, respectively. Hospital of stay also made a big difference for patients discharged to nursing homes. Only 13% of long-stay patients were discharged to a nursing home; 52% were discharged home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…This result is in agreement with other studies which found that patients with functional dependency, those requiring more assistance with their ADL, and patients with physical limitations were more at risk of experiencing delays in hospital discharge and remaining on acute care wards for non-acute reasons. 18,20,24 Third, along with several studies that showed older patients being at increased risk of experiencing hospital discharge delays, 11,18,19,[21][22][23] our results confirm that older age is a risk factor for remaining on an acute care ward for non-acute reasons. We observed only a 2% increased risk in a study population in which 53% were aged 75 years.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This result is in agreement with other studies which found that patients with functional dependency, those requiring more assistance with their ADL, and patients with physical limitations were more at risk of experiencing delays in hospital discharge and remaining on acute care wards for non-acute reasons. 18,20,24 Third, along with several studies that showed older patients being at increased risk of experiencing hospital discharge delays, 11,18,19,[21][22][23] our results confirm that older age is a risk factor for remaining on an acute care ward for non-acute reasons. We observed only a 2% increased risk in a study population in which 53% were aged 75 years.…”
Section: Resultssupporting
confidence: 86%
“…The factor that decreased the risk of being non-acute was having a feeding tube prior to hospital presentation (OR 0.50, 95% CI 0.31-0.83). 4,19,22,24 The multivariate model identified seven variables that are significantly associated with the non-acute status on day 30 of hospitalization. First, we found that cognitive impairment increases the likelihood of occupying an acute care bed for non-acute purposes by 61%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 This characteristic has been found to be associated with longer hospitalization. 51,52 Cognitively impaired patients remaining on an acute psychiatric care unit present a major concern, mainly because these settings are often unable to adequately meet these patients' needs. 53,54 Finally, 8 patients in the nonacute group had a total hospital LOS of greater than 100 days, with 1 patient staying as long as 153 days.…”
Section: Discussionmentioning
confidence: 99%
“…6,20 That said, ALC is a symptom of a poorly functioning healthcare system, 20 characterized by hospital process issues (delays in assessment or lack of consensus on next steps in care), [21][22][23] postacute care capacity issues (lack of timely and suitable housing, rehabilitation and home care services) 5,[23][24][25][26][27][28][29] or lack of long-term care beds (particularly beds that are tailored to the linguistic, cultural and geographical preferences of patients and caregivers). [30][31][32][33] Simply put, the ALC problem represents a mismatch between available care services and the needs of patients and their caregivers. The few studies on patient and caregiver ALC experience report that patients and caregivers feel overwhelmed, confused, excluded from care conversations and concerned about the next steps in the patient's care.…”
Section: Backg Rou N Dmentioning
confidence: 99%